2010
DOI: 10.4314/sajas.v39i1.61319
|View full text |Cite
|
Sign up to set email alerts
|

Association of the polymorphism in the 5’ flanking region of the ovine IGF-I gene with growth traits in the Baluchi sheep

Abstract: The insulin-like growth factor 1 (IGF-I) gene has been described in several studies as a candidate gene for growth traits in farm animals. The present preliminary study attempts to establish associations between growth traits and genetic polymorphisms at the 5' flanking region s IGF-I in the Baluchi sheep. The DNA of 102 sheep of the indigenous Iranian Baluchi breed was evaluated. Polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) analysis of the 5' flanking region (Exon1) of the ovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…The observed and expected genotypic and allelic frequencies of IGF-1 gene polymorphisms has been shown in Table 1. Almost the expected genotype frequencies were similar to Tahmoorespur et al (2009). This result suggested that genotype distribution was in the Hardy-Weinberg equilibrium (p<0.01), such as Yilmaz et al (2005).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The observed and expected genotypic and allelic frequencies of IGF-1 gene polymorphisms has been shown in Table 1. Almost the expected genotype frequencies were similar to Tahmoorespur et al (2009). This result suggested that genotype distribution was in the Hardy-Weinberg equilibrium (p<0.01), such as Yilmaz et al (2005).…”
Section: Discussionsupporting
confidence: 63%
“…Mehmannavaz et al (2010) proved a significant effect of IGF-1 polymorphism on EBVs for milk production traits on Holstein bulls. Tahmoorespur et al (2009) found the positive influence of exon1 in average daily Gain from Birth to Weaning (GBW).…”
Section: Resultsmentioning
confidence: 99%
“…This might also be related to the fact that for some of the SNPs, a low representation of alternative homozygotes was found in the studied population. However, associations of segregating SNPs in IGF1 and DGAT1 with growth, milk, and wool performance traits have been described in various sheep breeds such as Makeoi, Baluchi, Hu, Sarda, and Mehraban [55][56][57][58][59][60][61][62]. These breed differences might be due to artificial selection pressures or housing due to geographical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been only a few association analyses of the IGF-I gene polymorphism with growth traits in sheep. For example, , Tahmoorespur et al (2009), Negahdary et al (2013) and Gholibeikifard et al (2013) observed significant effects of the IGF-I gene polymorphism on several growth traits in Makooei and Baluchi sheep. Moreover, investigated the association of nucleotide substitution in the IGF-I gene with several body size traits in sheep.…”
mentioning
confidence: 99%